2008
DOI: 10.2176/nmc.48.495
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and Limitations of Fluorine-18-Fluorodeoxyglucose Positron Emission Tomography for the Detection of Malignancy of Orbital Tumors

Abstract: Fluorine-18-fluorodeoxyglucose positron emission tomography ([ 18 F]FDG PET) was assessed as a method for providing information about the malignancy of orbital tumors. Twelve patients with 13 orbital tumors underwent [ 18 F]FDG PET followed by biopsy or tumor removal via a transcranial approach. The accumulation ratio between the tumor and the contralateral normal tissue (T/N ratio) was calculated for 10 of the 13 lesions. The T/N ratio in benign lesions was compared with that in malignant tumors. Histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Miyamoto et al . [37] showed that semi-quantitative analysis was effective for the diagnosis of orbital tumors, with significantly higher tumor/controlateral normal tissue values in malignant than in benign lesions. Although little used, semi-quantitative analysis has been suggested by various authors, with the most used reference being the liver [49].…”
Section: Discussionmentioning
confidence: 99%
“…Miyamoto et al . [37] showed that semi-quantitative analysis was effective for the diagnosis of orbital tumors, with significantly higher tumor/controlateral normal tissue values in malignant than in benign lesions. Although little used, semi-quantitative analysis has been suggested by various authors, with the most used reference being the liver [49].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported an adult patient with fibrillary astrocytoma of the optic nerve showing isointense FDG uptake. Thus, PET CT may potentially play a role in the histological grading of ONG, especially in adult patients [ 19 ].…”
Section: Compartment-based Approach To Orbital Massesmentioning
confidence: 99%
“…Scinitigraphy using technetium 99 m-labelled red blood cells can help in the differential diagnosis of cavernous hemangioma from other imaging mimics [ 50 ]. Miyamoto et al have described two cases of adult orbital cavernous hemangiomas showing isointense FDG uptake on PET/CT [ 19 ].…”
Section: Compartment-based Approach To Orbital Massesmentioning
confidence: 99%
“…The main differential considerations for CN II lesion include optic pathway glioma (OPG), optic nerve sheath meningioma, idiopathic orbital inflammatory pseudotumor, and optic neuritis. FDG activity in Optic nerve glioma is variable depending on its histological grade [ 17 , 18 ]. Some authors suggested the use of FDG-PET/CT in monitoring malignant transformation of OPG in children with neurofibromatosis type 1 syndrome [ 17 , 19 ].…”
Section: Optic Nerve (Cn Ii)mentioning
confidence: 99%
“…3). Orbital pseudotumor could be both hyper or isometabolic on FDG PET [ 18 ]. Xie et al described a 56-year-old female with elevated FDG activity in several cranial and peripheral nerves suggestive of multiple neuritis, with patient“s symptoms improving following treatment [ 3 ].…”
Section: Optic Nerve (Cn Ii)mentioning
confidence: 99%